Pengenalan Cagar Budaya Pasar Gede Harjonagoro Surakarta Bagi Generasi Muda Melalui Video Time Lapse - Rudy W Herlambang; Mohammad Suharto; Jauhari .; Nadia Sigi Prameswari (PANTUN, 2017)
Cultural heritage which refers to objects among others are culturally protected materials, buildings, sites, and areas either in the land or in the water. Those culturally protected materials have signifcant values for history, knowledge, education, religion, and culture through the statement process. Surakarta City Planning Service owns 127 culturally protected buildings. Pasar Gede Harjonagoro is one of the cultural heritage functioning as the oldest traditional market; the centre of the people’s economic activities; and the sociocultural sphere of Surakarta society. Introducing cultural heritage to the youthcan be done by utilizing the technology sophistication. One of them is by designing audio visual by time lapse technique. Time lapse technique is the process of taking sequence frames of Surakarta cultural heritage with a certain duration. Audiovisual media are expected to increase new atraction and interest for the spectators. The result of the study is aimed to share knowledge and cultural education to all society in general and the youth in specifc.Keywords: Time lapse, culturally protected objects, cultural heritage, Pasar Harjonagoro Surakarta